Pathogenic mechanisms, diagnostics and clinical picture of seborrheic keratosis - L. A. Yusupovа; E. I. Yunusovа; Z. Sh. Garaeva; G. I. Mavlyutova; A. I. Arslanova (Лечащий Врач)
The article presents information about one of the most common and frequently encountered benign skin tumors seborrheic keratosis. Pathogenic mechanisms of seborrheic keratosis are described in detail, histological classification of skin tumors by WHO is given. The article describes several specific forms of this disease. Differential diagnostics and methods of treatment of patients with seborrheic keratosis are given.